Peculiarities of gunshot wound treatment of the wrist in modern conditions - Loskutov, Oleksandr; Bilyi, Sergey; Daragan, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The analysis of injuries as a result of military conflicts shows that gunshot wounds are 9–25 %. Objective: to find out the peculiarities of the gunshot wound treatment of the wrist at the stages of medical evacuation on the materials of the specialized center and to determine the most optimal options. Methods: results of the treatment of 238 victims are analyzed (average age 34.4 years) with wounds of the wrist and their consequences: fire-fighting — 135 (56.72 %), mines and explosives — 91 (38.24 %), explosives — 12 (5.04 %). Terms of hospitalization were 154 days after injury. Patients were divided into three groups: I —without complications (40.34 %); II — wound infection or tissue necrosis (32.77 %); III — consequences (26.89 %). Results: in the I group terms of treatment were (43.8 ± 1.16) days, in the II group — (64.4 ± 2.8) with the transfer to the next stages of rehabilitation. Treatment of the patients of the III group was conducted in prolonged terms with reconstructive surgeries. Conclusions: fire-fighting and mines and explosives wound (94.96 %) are prevailed in the structure of gunshot wounds. Timeliness, quality of primary surgical treatment of wounds, prevention of complications, planning and reconstructive surgeries on the wrist play a very important role in achievement of positive results. Inappropriate execution of the primary surgical treatment leads to an increase in the timing of treatment, appearance of additional anatomical and functional disorders and further reconstructive surgeries. Patients with isolated injuries after primary medical care of 0–II levels should be transferred to the stages of medical evacuation for the specialized care (III–IV level). In cases of complex injuries, in those who have pathological condition, emergency treatment in other medical establishments is in priority. Medical care by wrist surgeons on the place is relevant.